A systematic review and meta-analysis of the efficacy of the long-term treatment and support of substance use disorders. (September 2021) - Beaulieu, Myriam; Tremblay, Joël; Baudry, Claire; Pearson, Jessica; Bertrand, Karine
Abstract: Rationale: The reconceptualization of substance use disorders (SUD) as a chronic phenomenon calls for a paradigm shift in service provision, particularly by way of long-term treatment and support. Studies that have evaluated the efficacy of long-term treatment models seem to indicate that they are an improvement on more standard short-term treatments, even though these studies do not take the durations into consideration. Objective: Measure the efficacy of SUD treatments and support lasting 18 months or more regarding their ability to decrease substance use as compared to shorter treatments. Methods: A meta-analysis based on a systematic literature review was conducted. Eight databases were consulted for peer-reviewed studies. Certain variables were coded as moderators: intervention length, participant characteristics, and treatment characteristics. Results: The main results suggest that the people who received a planned long-term treatment or support had a 23.9 % greater chance of abstaining or consuming moderately than did people who received a shorter standard treatment (OR = 1.347 [CI 95 % = 1.087–1.668], p < .006, adjusted OR = 1.460 [CI 95 % = 1.145–1.861]). None of the moderation analyses revealed any variation in the efficacy of the long-term treatments and support. Conclusions: The reconceptualization of the SUD as a chronic disorder among people with this problem leads us to reconsider both the length of the services provided and the paradigms underlying their organization. Highlights: Substance use disorder treatments are usually short-term in nature. For some people, the substance use disorder may persist over time. Length of service is generally associated with better results. This meta-analysis evaluates the effectiveness of treatments of 18 months or more. The results show that these models have better results in reducing substance use.